2021
DOI: 10.1007/s10901-021-09874-5
|View full text |Cite
|
Sign up to set email alerts
|

Tenants’ residential mobility in Switzerland: the role of housing functions

Abstract: The interaction between residential preferences and dwellings is a complex system whose function thus far remains insufficiently explored. In this paper, we investigate housing functions as orchestrators of households’ residential mobility in the context of Swiss rental housing. We propose a theoretical multi-step model and use survey data from 878 Swiss tenants to inspect the model’s linkages. From the statistical analysis, we firstly observe that tenants’ residential satisfaction is more likely to increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In this exceptional setting, we observe that a change in ideal housing functions had occurred for the majority of the sample (60%), thereby corroborating previous studies that have shown how certain 'triggers' -e.g. a divorce, the birth of a child -can bring about a change in residential preferences (Brown and Moore 1970, Mulder and Hooimeijer 1999, Pagani and Binder 2021, Pagani et al 2021b).…”
Section: Results In Perspectivementioning
confidence: 99%
“…In this exceptional setting, we observe that a change in ideal housing functions had occurred for the majority of the sample (60%), thereby corroborating previous studies that have shown how certain 'triggers' -e.g. a divorce, the birth of a child -can bring about a change in residential preferences (Brown and Moore 1970, Mulder and Hooimeijer 1999, Pagani and Binder 2021, Pagani et al 2021b).…”
Section: Results In Perspectivementioning
confidence: 99%
“…An analysis of physical capital offers another dimension by which to assess energy vulnerability. There is a need to improve housing quality in Switzerland (Pagani et al, 2021), recognized in the national Energy Strategy 2050 which now provides tax incentives for building renovation (SFOE, 2021a) with a targeted reduction of 43% in energy consumption by 2,035 compared to 2000 levels (SFOE, 2021b). In all, of the approximately 1.5 million buildings in Switzerland, over 75% were built before 1980 and renovation is required for many of these (Frank, 2005).…”
Section: Physical Capital: Facilities/housingmentioning
confidence: 99%
“…In this process, the role of the economic challenge is more significant than that of social and environmental variables (Li, 2021). Since housing is closely tied to the identity of people (Naghizadeh, 2017), serving as a critical factor in securing citizenship rights (Zarghamifard, 2019), how urban living spaces are located and identified and at the same time accounting for quantitative and qualitative dimensions of the housing are among crucial issues in ecological research concerned with the urban system (Pilehvar, 2022), which provides more significant insights into complex human-environment interactions in the housing system (Pagani, 2021). In light of this trend, the cognition, and analysis of housing dimension with quantitative and qualitative variables on the one hand and the analysis of factors affecting the location and placement, on the other hand, is of paramount importance.…”
mentioning
confidence: 99%